Agency and behavior change in agri-food systems transformation: Lessons from the CGIAR Agroecology Initiative - Voss, Rachel C; Freed, Sarah; Falk, Thomas; Rietveld, Anne; Rahma, Adam; Alary, Véronique; Beltran, Marcela; Braiki, Houssem; Frija, Aymen; Guettou Djurfeldt, Nadia; Hamrouni, Dhia; Idoudi, Zied; et al. (2024)
Systems-level transformation is increasingly recognized as necessary to improve the sustainability, equity, and resilience of agri-food systems. The CGIAR Initiative on Agroecology uses a systems transformation approach in alignment with Gliessmann (2014) and the 13 principles of agroecology outlined by the HLPE (2019). This approach requires new understandings of actor agency and behavior change processes that enable systems change. To provide these new understandings for approaches and investments in agroecological transitions, our study presents a novel framework and lessons from past experiences in similar transitions that required changes in behavior and agency of food system actors. The specific objectives of this study were to 1. Understand how agroecology-relevant projects, government and/or donor programs, community initiatives, and social movements (collectively referred to as “initiatives” in this report) have approached behavior change and agency of food system actors for agri-food systems transformation; 2. Identify common assumptions on behavior change and agency that underpinned the initiatives’ design; and 3. Recommend adjustments to the Theories of Change, assumptions, and processes in initiative design and implementation to enhance the roles of actor agency and behavior change processes in systems change.